A pharmacokinetic model for voriconazole in a highly diversified population of children and adolescents with cancer. Issue 4 (20th February 2019) - Carlesse, Fabianne Altruda de Moraes Costa; de Araujo, Orlei Ribeiro; Marques, Leticia Maria Acioli; Silva, Dafne Cardoso Bourguignon da; Senerchia, Andreza Almeida; Petrilli, Antonio Sergio
Summary: Background: The wide pharmacokinetic variability of voriconazole leads to uncertainty regarding adequate exposure. Objectives: To create a pharmacokinetic model that could help to explain the variability. Methods: Retrospective review of paediatric patients with cancer. Models were built using Pmetrics. Results: We analysed 158 trough measurements in 55 patients; in 41.8%, the serum levels were between 1 and 6 mg/L on initial measurement. After the measurements, dosage adjustments were made in 42 (76.3%) patients, and the percentage of adequate levels rose to 54.5%. Fourteen deaths (25.4%) were attributed to invasive fungal diseases. The mean serum levels were higher in deceased patients (mean ± SD: 3.1 ± 3.2 mg/L vs 2.5 ± 3.6 mg/L in survivors; P  = 0.018), but the median doses per kg were higher in survivors. Drug exposure was also higher in deceased patients (mean ± SD of AUC: 19.2 ± 8.1 vs 9.5 ± 19.1 in survivors; P  = 0.005). No correlation was found between serum concentrations <1 mg/L and death attributable to fungal disease. Bioavailability was estimated in 50%. The maximum velocity of clearance was reduced in deceased patients. Conclusions: Extremely ill patients can be poor metabolizers of voriconazole. Therapeutic monitoring promotes only a limited improvement in drug management.